Microvascular lung vessels obstructive thromboinflammatory syndrome in patients with COVID-19: Insights from lung intravascular optical coherence tomography - Hajjar, Ludhmila Abrahão; Ancona, Marco B.; Filho, Roberto Kalil; Tresoldi, Moreno; Caldas, José Guilherme; Monti, Giacomo; Carnevale, Francisco Cesar; De Cobelli, Francesco; Moreira de Assis, André; Ciceri, Fabio; Landoni, Giovanni; Dijkstra, Jouke; et al. (Frontiers in Medicine, 2023)
Background Microvascular lung vessels obstructive thromboinflammatory syndrome has been proposed as a possible mechanism of respiratory failure in COVID-19 patients. However, it has only been observed in post-mortem studies and has never been documented in vivo, probably because of a lack of CT scan sensitivity in small pulmonary arteries. The aim of the present study was to assess the safety, tolerability, and diagnostic value of optical coherence tomography (OCT) for the assessment of patients with COVID-19 pneumonia for pulmonary microvascular thromboinflammatory syndrome. Methods The COVID-OCT trial was a multicenter, open-label, prospective, interventional clinical study. Two cohorts of patients were included in the study and underwent pulmonary OCT evaluation. Cohort A consisted of patients with COVID-19 with a negative CT scan for pulmonary thrombosis and elevated thromboinflammatory markers (D-dimer > 10,000 ng/mL or 5,000 < D-dimer < 10,000 ng/mL and one of: C-reactive Protein > 100 mg/dL, IL-6 > 6 pg/mL, or ferritin > 900 ng/L). Cohort B consisted of patients with COVID-19 and a CT scan positive for pulmonary thrombosis. The primary endpoints of the study were: (i) to evaluate the overall safety of OCT investigation in patients with COVID-19 pneumonia, and (ii) to report on the potential value of OCT as a novel diagnostic tool for the diagnosis of microvascular pulmonary thrombosis in COVID-19 patients. Results A total of 13 patients were enrolled. The mean number of OCT runs performed in each patient was 6.1 ± 2.0, both in ground glass and healthy lung areas, achieving a good evaluation of the distal pulmonary arteries. Overall, OCT runs identified microvascular thrombosis in 8 patients (61.5%): 5 cases of red thrombus, 1 case of white thrombus, and 2 cases of mixed thrombus. In Cohort A, the minimal lumen area was 3.5 ± 4.6 mm2, with stenosis of 60.9 ± 35.9% of the area, and the mean length of thrombus-containing lesions was 5.4 ± 3.0 mm. In Cohort B, the percentage area obstruction was 92.6 ± 2.6, and the mean thrombus-containing lesion length was 14.1 ± 13.9 mm. No peri-procedural complications occurred in any of the 13 patients. Conclusion OCT appears to be a safe and accurate method of evaluating the distal pulmonary arteries in hospitalized COVID-19 patients. Here, it enabled the first in vivo documentation of distal pulmonary arterial thrombosis in patients with elevated thromboinflammatory markers, even when their CT angiogram was negative for pulmonary thrombosis. Clinical trial registration ClinicalTrial.gov, identifier NCT04410549.